EFEKTIVITAS EDUKASI KONTRASEPSI JANGKA PANJANG MELALUI MEDIA VIDEO TIKTOK PADA WANITA USIA SUBUR DI DESA WONOREJO GONDANGREJO KARANGANYAR : - - Aris Prastyoningsih; Anita Sri Sulistyowati; Amrina Nur Rohmah (Jurnal Medicare, 2025)
Indonesia’s Total Fertility Rate (TFR) remains above the ASEAN average at 2.4 per 1000 women of reproductive age and has stagnated over the last four periods. In addition, the maternal mortality rate in Indonesia is still high at 359 per 100,000 live births. Long-acting reversible contraception (LARC) is the most effective method to reduce fertility rates, yet its utilization remains low at 20.3%. This study aimed to analyze the effect of education through TikTok video media on knowledge of LARC among women of reproductive age in Wonorejo Village, Gondangrejo. This quantitative study applied a pretest-posttest without control design with a total sample of 40 women of reproductive age. Data were analyzed using the Wilcoxon test. The results showed an increase in knowledge before and after audiovisual education through video, from 75% with good knowledge to 87.5%, with a p-value of 0.005. The study concludes that education through TikTok video media significantly improves knowledge about long-acting reversible contraception among women of reproductive age.